Patient-doctor ratio across nine super speciality clinics in government hospital: a cross sectional study - Pandey, Avinash; Singh, Anjana; Singh, Shivkant; Kumar, Amit (International Journal Of Community Medicine And Public Health, 2019)
Background: There is lack of information regarding patient-doctor ratio in government hospitals in India. The aim of the present study was to measure patient-doctor ratio across nine super specialty clinics. The objectives were to measure Outpatient department (OPD) patient-faculty and patient-senior resident doctor ratio, to measure number of patients seen per unit time and time spent per patient in OPDs across nine super specialty clinics. Methods: Total number of OPD patient visits in year 2018 was retrieved for cardiology, gastroenterology, gastrointestinal surgery, neurology, neurosurgery, nephrology, urology, paediatric surgery and oncology. Number of faculties and senior residents working in above specialties were obtained. Ratio of OPD patients to faculties and senior residents across nine above clinics were derived and compared. The average time spend per patient in OPDs across nine above clinics was calculated by number of working days in year 2018 and number of working hours or day in OPD clinics, excluding public holidays. Results: Total 3,59,099 OPD patient visits were registered in year 2018 across nine super specialty clinics. Patient to faculty ratio was highest for gastroenterology followed by neurology and cardiology, while least for neurosurgery and paediatric surgery in descending order. Gastroenterology, neurology and oncology OPDs saw more than 200 patients per working day; with average time spend per patient consultation was two minutes. Compared to super specialty physicians who spend average of 2.2 minutes per patient consult, surgical disciplines used an average of ten minutes per patient for consultation. Conclusions:Super specialty clinics in government hospitals are over worked and under staffed with heavy patient load. Multiple parallel clinics in concerned specialty will provide more time and quality of services per patient.